2021
DOI: 10.3390/ijerph182111685
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Low Self-Esteem and a Low Happiness Index Are Associated with Poor School Performance in Chilean Adolescents: A Cross-Sectional Analysis

Abstract: Objective: To analyze the relationship between anxiety, self-esteem, happiness index and primary school students’ academic performance in Chilean adolescents from the Biobío province. Methodology: 733 (46.1% girls; 12 (1.3 years)) public primary school students that completed the 2018 Health and School Performance Survey carried out in the Biobío province were included in this cross-sectional analysis. The BECK Anxiety Inventory (BAI) was used to measure anxiety while happiness index and self-esteem were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
7
1
Order By: Relevance
“…Although we found that high GPA was correlated with poor sleep, and that poor sleep was further correlated with poor mental health, we did not find a direct association between psychological measures and GPA. These results do not accord with studies reporting that students with poor mental health have poor academic performance [ 57 , 58 , 59 ]. It is possible that high-achieving students, such as medical or health science students, may have traits that make them more resilient which may mask any underlying mental suffering.…”
Section: Discussioncontrasting
confidence: 94%
“…Although we found that high GPA was correlated with poor sleep, and that poor sleep was further correlated with poor mental health, we did not find a direct association between psychological measures and GPA. These results do not accord with studies reporting that students with poor mental health have poor academic performance [ 57 , 58 , 59 ]. It is possible that high-achieving students, such as medical or health science students, may have traits that make them more resilient which may mask any underlying mental suffering.…”
Section: Discussioncontrasting
confidence: 94%
“…It was not possible to find in the existing literature instruments specifically used to evaluate the perception of cognitive factors in this specific age group. Although, these items are associated with the cognitive function perception in educational settings and have been used in other studies [ 48 ]. Hence, future studies could focus on the design of instruments to this end.…”
Section: Discussionmentioning
confidence: 99%
“…About the contributions to the education sciences, this study focuses on students’ self-perception a very relevant aspect associated with academic performance, considering the big number of mental health problems that Chilean students present, and which has not been studied in depth [ 48 , 49 ]. Another aspect contributing to the value of this study is the efforts in analyzing cognitive factors related to academic performance, in a group scarcely studied in Latin America, public elementary school students, with a representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…Roelen's research shows that ( 18 ), 15 years old and 17−18 years old are the two trough periods of teenagers' self-esteem development. According to Zapata-Lamana et al research ( 19 ), drug abuse, unmarried pregnancy, low academic achievement, campus violence, suicide, truancy, racing and other different ways in adolescent problems are all derived from their deep sense of self frustration, but they are eager to obtain a sense of achievement, so they can only meet their deep self-esteem needs in an abnormal way.…”
Section: Introductionmentioning
confidence: 99%